Drug lag and associated factors of orphan drugs approved by the U.S. in China - Mo, Qihui; He, Jiaqi; Guo, Qixiang; Yang, Yue (Frontiers in Pharmacology, 2025)
BackgroundA pronounced disparity exists in the accessibility of orphan drugs between China and developed countries, such as the United States. Identifying and analyzing the critical determinants that contribute to this gap is essential for enhancing the availability of orphan drugs and promoting equitable access for patients.MethodsWe included all new orphan drugs approved by the US Food and Drug Administration (FDA) between 2013 and 2023 and collected their approval information in China and the United States. Major factors of interest included accelerated review pathway, locations where pivotal clinical trials were conducted, therapeutic category, and other factors affecting the delay in drug launch. They were analyzed using multinomial logistic regression, analysis of covariance, and the Mann-Whitney U test.ResultsThe FDA approved a total of 242 new orphan drugs between 2013 and 2023. Among these, 119 (49.2%) of these drugs had been approved in China as of 1 January 2025, with a median lag time of 1,004 days (2.75 years). Among them, 47 drugs (41.2%) were included in the China’s List of Rare Diseases. Multinomial logistic regression analysis revealed that the conduct of pivotal trials supporting FDA approval in mainland China was associated with whether such drugs were launched in China (odds ratio = 10.53, 95% confidence interval 3.67–40.79; P < 0.001). Furthermore, the Mann-Whitney U test indicated that such characteristics as the inclusion of indications in China’s List of Rare Diseases, the granting of breakthrough therapy designation by the National Medical Products Administration (NMPA), and the inclusion of pivotal clinical trials in mainland China were all associated with the shortening of drug lag time.DiscussionOur findings suggest that orphan drug approval delays in China have improved significantly, but still face significant challenges. China’s involvement in the global collaborative development of drugs not only helps shorten the relative lag time for drugs to obtain approval in China but also avoids repeated trials and significantly improves R&D efficiency. We recommend that pharmaceutical companies include Chinese patients in the drug development stage so that they can enjoy cutting-edge innovative therapies more quickly.